Measuring the association between students’ exposure to social media and their valuation of sustainability in entrepreneurship - Barrera Verdugo, Gustavo Alfonso.; Villarroel Villarroel, Antonio José. (Elsevier, 2021)
Currently, university students can read content from various social media sites; however, little is known about the relationship between students' social media exposure and their valuation of sustainability in entrepreneurship and of environmental and social care as drivers of new venture creation. This research seeks to reduce this knowledge gap, evaluating discrepancies among undergraduates according to the intensity of their social media use. An online survey was applied to compare students’ perceptions based on their reading of Twitter, Facebook, Instagram, LinkedIn, and YouTube. A total of 143 valid responses of students in business and engineering careers in Chile were analysed using the Mann-Whitney test, showing a difference in the perceptions of undergraduates who read social media content once a day or more. The results show that a higher frequency of reading such content is related to higher perceived relevance of environmental sustainability, social welfare, and fair trade; likewise, it is linked with less perceived importance of sustainability as a driver of entrepreneurship. This evidence is relevant in recognizing the potential of social media sites to strengthen the higher education in sustainable entrepreneurship because these channels can be incorporated as a formal source of information for learning and its use is still limited. Future research should explore what specific types of content have the most significant impact on perceptions of sustainable entrepreneurship and promote particular methods for their application in this area.
Keywords: Higher education.; Online learning.; Entrepreneurship drivers.; Sustainability.; Social media.